Improving The Eighth Grade students' Reading Comprehension Achievement Through Jigsaw IV - Firmansyah, Martha Eka; Wijaputra, Bambang Arya; Andayani, Made Adi (English Education Study Program, 2022)
Abstract: this research was intended to improve the eighth grade students’ reading comprehension achievement and participation by using Jigsaw IV Technique in one of junior high schools at Bondowoso. The reaserch design was Class Action Research with the research participant were the VIII B grade. The average results of students’ participation in cycle 1 achieved the minimum target percentage that is 75% based on table 4.3. Besides, the result of reading comprehension test showed that there were 19 students (79%) achieved the criteria of success and 5 students (21%) got ≤ 65. Hence, Implementing Jigsaw IV could improve students’ reading comprehension achievement and students’ participation. Moreover, Jigsaw IV technique made the students actively participated in the teaching learning process and the Jigsaw IV activities were more interesting for the students. Jigsaw IV technique be able to accustomed the students to create cooperative situation in the class activities.